2008
DOI: 10.1590/s0101-20612008000400033
|View full text |Cite
|
Sign up to set email alerts
|

Validação de uma metodologia analítica para determinação de cálcio em produtos cárneos

Abstract: Em produtos cárneos, a concentração de cálcio depende do tipo de embutido e da quantidade de carne mecanicamente separada (CMS) utilizada para a sua fabricação. A legislação brasileira limita o uso de CMS nestes produtos (SOUZA et al., 2003).A metodologia analítica para determinação de cálcio em produtos cárneos recomendada pelo Ministério da Agricultura Pecuária e Abastecimento (MAPA), descrita em Brasil (1999), descreve em uma das etapas de filtração, a utilização de cadinho de Gooch e, como elemento filtran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 3 publications
0
8
0
1
Order By: Relevance
“…The absence of chemical interference was verified by the addition-and-recovery test, and the recovery rates ranged from 86 (S) to 116% (Zn). According to NBR ISO/IEC 17025, 35 the recovery tolerance ranges from 80 to 120%. Additionally, the accuracy was assessed by analyzing the SRM 1547, and it was attained good agreement, as indicated by Student's t-test at the 95% confidence limit; it was obtained recoveries (comparison between certified and experimental results) that ranged from 96.5 (S) to 101% (P).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of chemical interference was verified by the addition-and-recovery test, and the recovery rates ranged from 86 (S) to 116% (Zn). According to NBR ISO/IEC 17025, 35 the recovery tolerance ranges from 80 to 120%. Additionally, the accuracy was assessed by analyzing the SRM 1547, and it was attained good agreement, as indicated by Student's t-test at the 95% confidence limit; it was obtained recoveries (comparison between certified and experimental results) that ranged from 96.5 (S) to 101% (P).…”
Section: Resultsmentioning
confidence: 99%
“…20,52 Nonetheless, Fe applied to soil can be fixed in plant roots because of various chemical reactions 35,36 and due to the low mobility in plant tissue. The use of fertilizers containing inorganic forms or a chelate of Fe requires high concentrations to achieve a significant increase in the Fe concentration in the edible plant part.…”
Section: Effects Of Enrichment On Fe Bioaccessibilitymentioning
confidence: 99%
“…The obtained concentrations are shown in Tables 1 and 4. Several literature data have shown that meat and meat products in general have in their composition low concentrations of Ca. 14,30 However, according to the results in Tables 1 and 4, relatively high levels of this element were found in sausages and meatballs sample. This can be justified from the nature of the raw material used to manufacture these meat products, once that they are mechanically separated and the obtained part from leftover meat that remains attached to the bones after removing the bones.…”
Section: Analytical Resultsmentioning
confidence: 91%
“…The development of analytical methods for quality control processes is very important in order to monitor the chemical composition of these foods. [12][13][14] The most conventional sample preparation methods used for the determination of metals in food samples using spectroanalytical methods, involve the digestion of the sample with acids that have oxidant characteristics, using a digester block or microwave heating. 15 However, many of these procedures are tedious, require complex laboratory equipment, and increase the risk of contamination and analyte loss by volatilization or adsorption in flasks.…”
Section: Introductionmentioning
confidence: 99%
“…A segunda mudança foià remoção da etapa de lavagem com hexano. Os resultados da linearidade da metodologia na faixa de trabalho dependem da sensibilidade do equipamento utilizado, complexidade do método, reagentes utilizados, extração do analito, condições do equipamento e do meio ambiente, além da habilidade do analista [27]. O método demonstrou boa linearidade, R = 0,9978, sendo que, segundo a ANVISA e o INMETRO, as soluções preparadas apresentaram leituras de absorção diretamente proporcionaisà concentração do analito na amostra, dentro de um intervalo específico, confirmando a linearidade do método.…”
Section: Robustezunclassified